THE CORRELATION BETWEEN STUDENTS’ ONLINE LEARNING READINESS AND THEIR ENGLISH LEARNING ACHIEVEMENT - Zikriyah Zikriyah; Nurdin Noni; Maemuna Muhayyang (JTechLP: Journal of Technology in Language Pedagogy, 2022)
This research aims to determine the students’ level of online learning readiness, their English learning achievement, and to describe whether there is a significant correlation between those two variables. The population of this research was the students of English Education 2019, Faculty of Languages and Literature, Universitas Negeri Makassar with a total of 148 students and taking 37 students as a sample using purposive sampling. The design of this research is quantitative correlational research. The data were collected using the OLRS questionnaire (developed by Hung et al. (2010)) with a Likert model scale. Analysis of the data in this research was using the SPSS 25 program. The results of this research indicate that: (1) The students’ level of online learning readiness was in "ready go ahead" level for online learning (4.39), (2) The students' final score was in "very good" category (3.78), (3) The correlation analysis between the two variables showed a significant value (0.00) and a Pearson correlation (+969), which indicates that there is a significant correlation between students’ online learning readiness and their English learning achievement. The implication of this research is need to encourage students to pay more attention to five online learning readiness dimensions, especially in learner control dimension, because if all dimensions work simultaneously, they can affect students’ English learning achievement.